Characteristic systemic cytokine responses in children with human bocavirus‐positive lower respiratory tract infection. (March 2014) - Hirose, Yosuke; Hamada, Hiromichi; Wakui, Taku; Ogawa, Tomoko; Terai, Masaru
ABSTRACT To investigate systemic cytokine responses in human bocavirus (HBoV)‐associated lower respiratory tract infection, serum cytokine profiles were analyzed in HBoV positive‐children (n = 14) using multiplex immunoassay. Concentrations of TNF‐α, IL‐2, IL‐5 and IL‐8 on admission were significantly different from those of respiratory syncytial virus‐positive children (n = 28). This unique cytokine response might partly explain some characteristic clinical features of HBoV‐associated respiratory infection.